Measuring student performance in job market through industrial training: A study at Universiti Utara Malaysia - Mahat, Nor Idayu; Chik, Abdul Razak; Hassan, Shahizan; Yahya, Mohd Azlan; Lim, Khong Chiu (Common Ground Publishing, 2009)
There is a lack of studies that investigate the impact of industrial training on university students. To fill this gap, a study was carried out to investigate and consequently measure the performance of students of Universiti Utara Malaysia (UUM) who are undertaking their industrial training in various organisations of different industrial backgrounds. Five skills are measured including students’ knowledge on basic knowledge, communication skills, attitude and discipline, hands-on skills and leadership. Questionnaire was sent to all organisations which participate in UUM’s industrial training programme and a total of 438 responded.The initial feedback indicated that industrial training is viewed by the respondents as essential and would benefit both university and the industry.The performances showed by the students are satisfactory and, in general, fulfil the organisations’ needs. The respondents also forwarded some interesting suggestions and ideas on how to improvise efforts to strengthen students’ skills.